“Queen of the Picket Line”: Beauty Contests in the Post–World War II Canadian Labor Movement, 1945–1970 - Sangster, Joan (Labor, 2008)
This article examines the proliferation of beauty contests sponsored by the union movement after World War II, as a means of exploring the contradictions of the Fordist accord for women workers, and also feminist scholarship on beauty and the body. Beauty contests were articulations of labor pride and identity; they reflected the popular culture of the post-war period, labor's search for respectability, and labor's attempts to entice women into the movement by appealing to women's culture. A few contests even offered more subversive meanings of beauty by celebrating the `queen of the picket line.' However, most labor beauty contests promoted competitive individualism, consumption, and images of passive femininity that kept women marginalized on the sidelines of the labor movements. Le Bal des Midinettes, sponsored by the ILGWU, was an excellent example of these contradictions, espousing both faith in the Cinderella myth and a sense of French Canadian working-class pride. While theories stressing identity, agency, and subjectivity offer some insights into beauty contests, feminist-materialist analyses of commodification, exploitation, and ideology remain essential to our understanding of their meaning for, and impact on women workers in this period.